Yo sup??
The words that might fit will be
always
sometimes
never
sometimes
Hope this helps.
Answer:
part A: expression 1: 6(8m+2)
expression 2: 6m+12+42m
Part B: 6(m+2+7m)= 6(8m+2)
combine like terms is 6(m+2+7m), so it is 6(2+8m) or 6(8m+2)
6(8m+2)= 6(8m+2)
Part C: 6m+12+42m=6(m+2+7m)
m=0
6(0+2+7(0))=6(0)+12+42(0)
6(2)= 12
12=12
Answer:
thats why its switches on my glee
Step-by-step explanation:
Answer:
7
Step-by-step explanation:
15-8=7 this is how you answer it
Answer:
43
Step-by-step explanation:
31+12=43
Therefore adding 43 to -31 should give the answer 12.